Efficiency Analysis of the Combination of Heavy Equipment Use in Excavation and Landfill Work in Road Construction Projects - Usman Hadianto; I Nyoman Dita Pahang Putra (Indonesian Journal Publisher, 2025)
An efficient heavy equipment management system is needed to complete a earthwork on time. This study aims to analyze the productivity and efficiency of the combination of heavy equipment used in excavation and heap work. Heavy equipment productivity is calculated based on cycle time in the field and its needs are calculated based on the volume of the weekly plan. After that, an efficient combination of heavy equipment planning is carried out for excavation and heaping work. The method of calculating heavy equipment needs uses a theoretical approach, with cycle time adjustments based on operational conditions in the field. Efficiency analysis and heavy equipment selection are carried out based on the idle time of the smallest heavy equipment. The Optimal cut-fill Pairing and Sequencing (OPS) method is used to create a scheme of excavation and heaping work. The results of the analysis showed that the most efficient combination of heavy equipment used in excavation work of 14,467.66 BCM every week was 4 units of Kobelco PC 200 excavators, 2 units of Kobelco SK 330 excavators, and 10 units of Hino 500 dump trucks. Meanwhile, in the backfill work of 5,423.96 CCM every week, 1 unit of Komatsu D68ESS bulldozer, 1 unit of Sakai SV512TF sheepfoot roller, and 1 unit of Sakai vibro roller SV512TF are needed. This combination is chosen based on the value of the smallest idle time. With proper planning, high work efficiency, operational cost savings, and project completion are achieved according to the set schedule